2002
DOI: 10.1038/sj.mp.4000919
|View full text |Cite
|
Sign up to set email alerts
|

Preferential transmission of interleukin-1 receptor antagonist alleles in attention deficit hyperactivity disorder

Abstract: Keywords: attention deficit hyperactivity disorder; ADHD; interleukin-1 receptor antagonist gene; transmission disequilibrium test

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Indeed, IL-1β, TNFα, and IL-6 have been implicated as having roles in synaptic plasticity in the hippocampus (Balschun et al 2004; Goshen and Yirmiya 2009; Schneider et al 1998) and can activate astrocytes that modulate synaptic plasticity. Furthermore, IL-1 receptor antagonist polymorphism has been implicated in ADHD (attention deficit hyperactivity disorder) etiopathogenesis (Segman et al 2002), and disrupted attention has been observed previously in our male CAPs-exposed mice (Allen et al 2013). Furthermore, hippocampal GLU in CAPs-exposed males was positively correlated with hippocampal IL-1β/IL-6, likely indicating a mechanistic link between excitotoxicity and neuroinflammatory responses.…”
Section: Discussionsupporting
confidence: 57%
“…Indeed, IL-1β, TNFα, and IL-6 have been implicated as having roles in synaptic plasticity in the hippocampus (Balschun et al 2004; Goshen and Yirmiya 2009; Schneider et al 1998) and can activate astrocytes that modulate synaptic plasticity. Furthermore, IL-1 receptor antagonist polymorphism has been implicated in ADHD (attention deficit hyperactivity disorder) etiopathogenesis (Segman et al 2002), and disrupted attention has been observed previously in our male CAPs-exposed mice (Allen et al 2013). Furthermore, hippocampal GLU in CAPs-exposed males was positively correlated with hippocampal IL-1β/IL-6, likely indicating a mechanistic link between excitotoxicity and neuroinflammatory responses.…”
Section: Discussionsupporting
confidence: 57%
“…In contrast, intracerebral injection of IL-1RA worsened learning and memory in a variety of animal models [47,48] and, blocking of the IL-1ß receptor by IL-1RA during the LTP process in the hippocampus, impaired the maintenance of LTP [49,50]. Some studies have also explored the polymorphic variations of IL-1RA [51,52] in association with attention deficit hyperactivity disorder, but with conflicting results.…”
Section: Id Patients Controlsmentioning
confidence: 86%
“…The IL-1RA is a molecule that competes for receptor binding with IL-1a and IL-1b, blocking their role in immune activation. Polymorphisms in IL-1Ra gene, IL1RN, have been directly associated with ADHD (Segman et al 2002). For the inheritance of alleles of an intronic 86-bp VNTR polymorphism, investigators reported significant evidence for biased transmission of the 4-repeat allele.…”
Section: Genetics Of Adhd and Inflammation Signallingmentioning
confidence: 99%